Phylogenetic and genetic characterization of influenza A H9N2 viruses isolated from backyard poultry in selected farms in Ghana. Issue 4 (21st April 2022) - Kotey, Erasmus Nikoi; Asante, Ivy Asantewaa; Adusei‐Poku, Mildred; Arjarquah, Augustina; Ampadu, Richard; Rodgers, David; Nyarko, Edward Owusu; Asiedu, William; Dafeamekpor, Courage; Wiley, Michael R.; Mawuli, Gifty; Obeng, Richard Asomadu; et al.
Abstract: Introduction: Avian influenza viruses (AIV) cause significant economic losses to poultry farmers worldwide. These viruses have the ability to spread rapidly, infect entire poultry flocks, and can pose a threat to human health. The National Influenza Centre (NIC) at the Noguchi Memorial Institute for Medical Research in collaboration with the Ghana Armed forces (GAF) and the U.S. Naval Medical Research Unit No. 3, Ghana Detachment (NAMRU‐3) performs biannual surveillance for influenza viruses among poultry at military barracks throughout Ghana. This study presents poultry surveillance data from the years 2017 to 2019. Methodology: Tracheal and cloacal swabs from sick and healthy poultry were collected from the backyards of GAF personnel living quarters and transported at 4°C to the NIC. Viral ribonucleic acid (RNA) was isolated and analyzed for the presence of influenza viruses using real‐time polymerase chain reaction (PCR) assays. Viral nucleic acids extracted from influenza A‐positive specimens were sequenced using universal influenza A‐specific primers. Results: Influenza A H9N2 virus was detected in 11 avian species out of 2000 samples tested. Phylogenetic analysis of viral haemagglutinin (HA) protein confirms the possibility of importation of viruses from North Africa and Burkina Faso. Although the detected viruses possess molecular markers of virulence and mammalian host adaptation, the HA cleavage site anlaysis confirmed low pathogenicity of the viruses. Conclusions: These findings confirm the ongoing spread of H9 viruses among poultry in Ghana. Poultry farmers need to be vigilant for sick birds and take the appropriate public health steps to limit the spread to other animals and spillover to humans. Abstract : Our study confirms the spread of H9 viruses among poultry in Ghana. Poultry farmers need to be vigilant for sick birds and take the appropriate public health steps to limit the spread to other animals and spillover to humans.